Risk and Expected Utility Theory - Robin Pope; Reinhard Selten (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
The paper re-expresses and complements arguments against the normative validity of expected utility theory in Robin Pope (1983, 1991a, 1991b, 1985, 1995, 2000, 2001, 2005,2006, 2007). The objections concern the neglect of the evolving stages of knowledge ahead (stages of what the future will bring) when such evolution is fundamental to an experience of risk. This neglect entails a disregard of emotional and financial effects on well-being before a particular risk is resolved. Problems of the time structure of risk are investigated in a simple temporal framework restricted to a subclass of temporal lotteries in the sense of David Kreps and Evan Porteus (1978). This subclass is narrow but wide enough to discuss basic issues. It will be shown that there are serious objections against the modification of expected utility theory axiomatised by Kreps and Porteus (1978, 1979). By contrast the umbrella theory proffered by Pope that she has now termed SKAT, the Stages of Knowledge Ahead Theory, offers an epistemically consistent framework within which to construct particular models to deal with particular decision situations. A model by Caplin and Leahy (2001) will also be discussed and contrasted with the modelling within SKAT (Pope, Leopold and Leitner 2006).
Keywords: 330; Entscheidung bei Risiko; Erwartungsnutzen; Kritik; Theorie